2020
DOI: 10.1016/j.archoralbio.2019.104621
|View full text |Cite
|
Sign up to set email alerts
|

Effects of spaceflight on the mouse submandibular gland

Abstract: Objective: This study was conducted to determine if the morphology and biochemistry of the mouse submandibular gland is affected by microgravity and the spaceflight environment.Design: Tissues from female mice flown on the US space shuttle missions Space Transportation System (STS)-131 and STS-135 for 15 and 13 d, respectively, and from male mice flown on the 30 d Russian Bion-M1 biosatellite, were examined using transmission electron microscopy and light and electron microscopic immunohistochemistry. Results:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 79 publications
0
3
0
1
Order By: Relevance
“…In the CRS-10 mission, incisors of SF animals demonstrated an increase in pulp area with a corresponding decrease in hard tissue area in cross-sectional samples, which may be suggestive of altered morphology ( Maupin et al 2019 ). Moreover, changes in salivary glands have been described in spacefarers, which may also contribute to microgravity-induced changes in teeth, as saliva is well known for its protective function ( Hand et al 2020 ). Thus, more data are needed to fully understand the effect of spaceflight on teeth structure.…”
Section: Discussionmentioning
confidence: 99%
“…In the CRS-10 mission, incisors of SF animals demonstrated an increase in pulp area with a corresponding decrease in hard tissue area in cross-sectional samples, which may be suggestive of altered morphology ( Maupin et al 2019 ). Moreover, changes in salivary glands have been described in spacefarers, which may also contribute to microgravity-induced changes in teeth, as saliva is well known for its protective function ( Hand et al 2020 ). Thus, more data are needed to fully understand the effect of spaceflight on teeth structure.…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, oral microorganisms are closely associated with oral diseases such as caries ( Dinis et al, 2022 ), periodontitis ( Plachokova et al, 2021 ), and oral cancer ( Zhang et al, 2019 ); they are also involved in various systemic diseases such as diabetes ( Matsha et al, 2020 ), Alzheimer’s disease ( Dominy et al, 2019 ), pancreatic cancer ( Fan et al, 2018 ), and colorectal cancer ( Wang et al, 2021 ). Previous and recent studies have also suggested that oral soft and hard tissues, including salivary glands ( Groza et al, 1981 , 1983 ; Mednieks and Hand, 1987 ; Mednieks et al, 2014 ; Dagdeviren et al, 2018a ; Hand et al, 2020 ), mandibles ( Simmons et al, 1983 ; Ghosh et al, 2016 ; Dagdeviren et al, 2018b ), and teeth ( Rosenberg et al, 1984 ; Dagdeviren et al, 2018b ), are affected by spaceflight. The risk of dental diseases, such as caries and periodontitis, increases in a microgravity environment ( Rai and Kaur, 2011 ).…”
Section: Introductionmentioning
confidence: 98%
“…The digestive system is highly sensitive to space flight factors, which can limit the functionality of astronauts on board the ISS [9]. As reported, significant changes occur in the digestive organs under space flight conditions [8][9][10][11], including a decreased evacuation function of the gastric contents, an increased content of gastric fluid, and an expansion of the intestine, which indicate an increased secretory activity in the organs [1]. In addition, studies have revealed structural changes in the mucosa and other layers of the stomach and intestines, resulting in a risk of progressive accumulation of changes at the tissue level up to the formation of morphological signs of atrophy and a loss of muscle mass [12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%